Efforts to Increase Knowledge about Adolescent Reproductive Health through Counseling at the Bejiruyung Healthy Youth Forum (Fresh Beji) in Bejiruyung Village, Sempor District, Kebumen Regency - Wulan Rahmadhani; Siti Mutoharoh; Kusumastuti; Adinda Putri Sari Dewi (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
15% of the total population in Indonesia were teenagers. Adolescent is a critical period which is changed from childhood to adulthood. There are many problems in this periode included reproductive health problem releted to sexual behaviour. The problem happened cause of the curiosity of something to big. The aimed of this activity was to increase adolescent knowledge about reproductive health properly. Method in this study was counseling and meansuring tool used a questionnaire that will be filles ouy by adolescent before and after counseling. 25 adolescents were selected became respondents. Result in this study was the knowledge of adolescent about reproductive health was increase. Respondents were enthusiastic which was indicated by the number of questions during the questions and answer session. Adolescent periode was the most rapid development in the course of his life. Therefore, efforts are needed to improve or educate related toreproduktif helath to prevent wrong behavior on adolescent.